2021
DOI: 10.1186/s12301-020-00110-0
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and implementation of lonizing radiation safety measures among urology community in Egypt: nationwide survey

Abstract: Background To assess awareness of ionizing radiation safety measures among Egyptian Urology Trainees and Urologists and see the effect of radiation safety courses on the adoption of these measures. Methods This Internet-based survey was conducted via https://www.surveymonkey.com/ after approval by the Egyptian Urological Association (EUA). It was sent to all EUA members via email during December 2019. Participation was voluntary and questions inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Similar to the present study, Omar et al (2021) conducted a survey to assess the awareness, training, and implementation of ionizing radiation safety measures among Egyptian trainees and urologists and evaluate the safety measures taken during diagnosis and treatment in urology practice in Egypt. In this study, a considerable number of responses from residents, specialists, consultants, and professors were received.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the present study, Omar et al (2021) conducted a survey to assess the awareness, training, and implementation of ionizing radiation safety measures among Egyptian trainees and urologists and evaluate the safety measures taken during diagnosis and treatment in urology practice in Egypt. In this study, a considerable number of responses from residents, specialists, consultants, and professors were received.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with participants who did not receive a radiation safety course, participants who received a radiation safety course had significantly shorter fluoroscopy time during Ureteroscopy (31±17 vs. 131±181), Percutaneous nephrolithotomy (137±84 vs. 413±556). Omar et al (2021) concluded that more radiation safety awareness among Egyptian urology trainees and urologists is required. Respondents who received a radiation safety course showed significantly shorter fluoroscopy time during end-urologic procedures.…”
Section: Discussionmentioning
confidence: 99%